2014
DOI: 10.1049/el.2014.0903
|View full text |Cite
|
Sign up to set email alerts
|

Object‐based attention: saliency detection using contrast via background prototypes

Abstract: An object-based attention model to predict visual saliency using contrast against the 'background prototypes' is presented. The proposed model automatically identifies a series of regions far away from the image centre as background prototypes. The visual saliency is then calculated using the colour contrast against these background prototypes. Promising experimental results demonstrate the effectiveness of the proposed model in terms of detection accuracy and implementation efficiency.Introduction: The human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Extensive experiments on two publicly available databases such as DUT-OMRON [5] and ECSSD [6], show that by incorporating image content information, the proposed model leads to significantly improved quality prediction accuracy. Furthermore, we also validate the applicability of the proposed method in selecting optimal saliency map from a set of candidates for improving the performance of saliency detection [7], [8] and segmentation [3], [9]. The results demonstrate that the optimal selection by our method can significantly outperforms the best saliency detection al-Copyright c 2019 The Institute of Electronics, Information and Communication Engineers gorithms and existing quality assessment methods for both the saliency detection and saliency segmentation.…”
Section: Introductionmentioning
confidence: 59%
“…Extensive experiments on two publicly available databases such as DUT-OMRON [5] and ECSSD [6], show that by incorporating image content information, the proposed model leads to significantly improved quality prediction accuracy. Furthermore, we also validate the applicability of the proposed method in selecting optimal saliency map from a set of candidates for improving the performance of saliency detection [7], [8] and segmentation [3], [9]. The results demonstrate that the optimal selection by our method can significantly outperforms the best saliency detection al-Copyright c 2019 The Institute of Electronics, Information and Communication Engineers gorithms and existing quality assessment methods for both the saliency detection and saliency segmentation.…”
Section: Introductionmentioning
confidence: 59%
“…Cheng et al [17] demonstrated two saliency models: histogram-based contrast (HC), which assigns a pixel-wise saliency value, as well as region-based contrast (RC), which incorporates spatial relations at the cost of reduced computational efficiency. Zhou [25] proposed an object-based attention model that automatically identifies a series of regions far away from the image center as background prototypes. Zhou et al [26] combined widely used contrast measurements, namely, center-surround, corner-surround, and global contrast, to detect visual saliency.…”
Section: Related Workmentioning
confidence: 99%
“…In the bottom‐top saliency methods, low‐level features are used to extract the saliency map [14, 15]. These features encompass colour, texture, brightness levels, etc.…”
Section: Related Workmentioning
confidence: 99%